Molar Incisor Hypomineralization: Awareness among Postdoctoral Dental Residents: A Cross-Sectional Study - Jana Negrescu; Laurenc Kodra; Hassan Ziada; Tanya Al-Talib; Neamat Hassan Abubakr (MDPI AG, 2022)
Background: Molar incisor hypomineralization (MIH) is the presentation of an enamel defect, where incisors and one (or more) molars are affected. Identifying MIH is significant in restoring its visual defect and avoiding pain or other consequences of this condition. The present cross-sectional study aimed to evaluate the awareness, ability, and confidence in identifying MIH among postgraduate residents in the state of Nevada. Methods: This cross-sectional study was conducted among postdoctoral dental residents at the School of Dental Medicine, University of Nevada, Las Vegas. This cross-sectional study used images of cases of MIH and a survey to collect the data. The survey included demographics, educational background, and basic knowledge of MIH. Results: The response rate to the invitation to participate was 91%. The confidence in identifying MIH was 100%, 50%, and 33.3% for pediatric, orthodontic, and general practice residency (GPR). A total of 70% were aware of this anomaly from their predoctoral dental education and indicated the need for further related education. There was 33% confusion with fluorosis and 16.6% with amelogenesis imperfecta. A total of 66.6% of the participants indicated that they require further education relating to MIH. Conclusion: Within the limitations of the present investigation, MIH awareness among the investigated groups varied but was highest amongst the pediatric residents.